Distributed admission control for QoS and SLS management - Lima, Solange (2004)
This article proposes a distributed admission control (AC) model based on on-line monitoring to manage the quality of Internet services and Service Level Specifications (SLSs) in class-based networks. The AC strategy covers intra- and interdomain operation, without adding significant complexity to the network control plane and involving only edge nodes. While ingress nodes perform implicit or explicit AC resorting to service-oriented rules for SLS and QoS parameters control, egress nodes collect service metrics providing them as inputs for AC. The end-to-end operation is viewed as a cumulative and repetitive process of AC and available service computation.We discuss crucial key points of the model implementation and evaluate its two main components: themonitoring process and the AC criteria. The results show that, using proper AC rules and safety margins, service commitments can be efficiently satisfied, and the simplicity and flexibility of the model can be explored to manage successfully QoS requirements of multiple Internet services.